2006
DOI: 10.1007/s10800-006-9196-x
|View full text |Cite
|
Sign up to set email alerts
|

Rinsing effect of alkaline electrolyzed water on nickel surfaces

Abstract: The improvement in the surface cleanliness of electroplated nickel by rinsing in alkaline electrolyzed water (AEW) was determined. When the nickel plated sample was rinsed with the AEW, it was found that the amount of residual sulfate ion on the surface of a sample decreased approximately by half compared to one rinsed only with de-ionized pure water. Because nanosize hydrogen bubbles are present in the AEW, and the zeta-potential has a negative value, we then surmised that the mechanism of rinsing was as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…For removal of ionic impurities including sulfate ions, various techniques are used during cleaning after plating: repeated cleaning with pure water, ultrasonic cleaning, or the like. In a previous article, we reported that cleaning with pure water after a nickel-plated specimen was once immersed into AEW (hereinafter, rinsing) was able to decrease the amount of sulfate ions remaining on the nickel-plated surface [5]. Results of this study verified our idea that the rinse effects of AEW are attributable to hydrogen bubbles generated in AEW, particularly nanosize hydrogen bubbles (hereinafter, hydrogen nanobubbles).…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…For removal of ionic impurities including sulfate ions, various techniques are used during cleaning after plating: repeated cleaning with pure water, ultrasonic cleaning, or the like. In a previous article, we reported that cleaning with pure water after a nickel-plated specimen was once immersed into AEW (hereinafter, rinsing) was able to decrease the amount of sulfate ions remaining on the nickel-plated surface [5]. Results of this study verified our idea that the rinse effects of AEW are attributable to hydrogen bubbles generated in AEW, particularly nanosize hydrogen bubbles (hereinafter, hydrogen nanobubbles).…”
Section: Introductionsupporting
confidence: 81%
“…Experiments were performed according to the following steps to verify that AEW rinses away sulfate ions [5]:…”
Section: Rinse Effect Experiments By Aewmentioning
confidence: 99%
See 2 more Smart Citations